MAQĀṢID AL-SHARĪʿAH AL-SHATIBI IN THE DIGITAL ERA: CONTEMPORARY PERSPECTIVES ON HALAL LIFESTYLE AND TECHNOLOGY IN INDONESIA - Lestianingsih, Eneng Nenden; Ahyani, Hisam; Muharir; Lathif, Agus Munjirin Mukhotib; Lousada, Sérgio António Neves; Mutmainah, Naeli; Atiqoh, Umi (Universitas Islam Indonesia, 2025)
Purpose - This research aims to analyze the application of Maqāṣid al-Sharīʿah principles according to al-Shatibi in the context of the halal lifestyle in the digital era. The main focus of this research is how digital technology, such as halal e-commerce platforms and digital halal marker applications, can facilitate access and transparency of halal products. In addition, this study examines the relevance of Maqāṣid al-Sharīʿah principles in the contemporary Islamic legal framework in facing the challenges of regulation and validity of halal information. Methods - This research uses a qualitative method with a literature review approach and case analysis. Data is collected through literature studies related to digital halal regulations and studies on technology implementation in supporting halal lifestyles. Findings - The results show that digital technology plays a role in strengthening halal lifestyles through innovations that increase accessibility and transparency. However, challenges such as unverified information, evolving regulations, and potential deviations from Shariah principles must be addressed. Collaboration between government, industry, and society is key to overcoming these challenges. Contribution/Limitation - This research contributes to understanding the relationship between Maqāṣid al-Sharīʿah, digital technology, and contemporary Islamic law in supporting halal lifestyle. However, this research is still limited to literature analysis and does not include empirical research on halal technology users in Indonesia. Originality/Value - This research offers new insights into the integration of technology in the principles of Maqāṣid al-Sharīʿah in contemporary Islamic law.